The 12-th International Symposium on Sound and Vision Engineering and Mastering - ISSVEM’07 - Archives of Acoustics, Editorial Board (Archives of Acoustics, 2007)
Gdańsk, Poland, June 15-17, 2007 The 12-th International Symposium on Sound and Vision Engineering and Mastering (ISSVEM’07) was organized by the Multimedia Systems Department of the Gdańsk University of Technology under the auspices of the Polish Section of the Audio Engineering Society and the Polish Academy of Sciences. The conference was held on June 15-16, 2007 in Gdańsk, Poland. The conference was hosted by the Multimedia Systems Department (URL address: http://www.multimed.org/issvem07). The Symposium gathered interdisciplinary mixture of respectful engineering and musicologists scientists and specialists. Consequently, this conference was designed to combine future perspectives along with state-of-the-art research and practice in the interdisciplinary music and technical domains. The Symposium started with two joint sessions co-organized by the Scientific Committees of the KKRRiT’2007 conference (hosted by the Department of Radiocommunication Systems and Networks, GUT and ISSVEM’07. The first session was entitled: "Tools for multimedia data analysis and compression and plenary session". The Symposium was officially opened by Prof. Andrzej Czyżewski during the first plenary session. The plenary speakers were: Kristian Kroschel and Michael Grimm form the University of Karlsruhe, Germany who presented a paper entitled: "Audio-visual emotion detection" and the second paper was given by Wiesław Woszczyk, President of the Audio Engineering Society (McGill University, Canada). The second plenary session included a paper by Andrzej Rakowski, Sylwia Makomaska, and Piotr Rogowski from the Fryderyk Chopin Academy of Music in Warsaw, entitled: "Short-term memory for pitch in absolute-pitch possessors" and a paper presented by Wieslaw Woszczyk on "High-resolution multisensory communication using broadband networks - McGill UltraVideo". The conference included also regular sessions given by experts in the specific subject areas on the topics such as: Musical Informatics, Sound and Vision Perception and Measurement, and Electroacoustic Devices and Systems. In addition there was a poster session scheduled with papers on sound and video restoration, animation, and a presentation of students’ recordings. The Symposium program included also a visit and presentation of the Polish Baltic Philharmonic Hall.